Looking for Oil-free Building Materials Clay Pipes to Replace Polymer Pipes. (2016) - Salha, Riyadh; Tosa, Florin V.
Abstract: After centuries of environmental pollution, many studies have illustrated the impact of oil and its products over the surrounding environment. Therefore, as a step toward sustainable neighbourhoods, it may an idea to search for alternative oil-free building materials. On the other hand, plastic is considered the main building material that derived from oil and used in a wide-range as (water system pipes, insulation material, plastic fibre for reinforcement concrete, etc.). However, it is enough for these materials to be derived from oil to be polluting materials, but they are also strange materials to nature that they take thousands of years to decompose. Moreover, some materials like polystyrene it is not even accepted yet to be recycled because of the economic point of view. All above has urged us to search for alternative eco-friendly materials, thus the natural materials that come from the earth like clay may be that one. So these papers are going to present the possibility of replacing plastic pipes with clay ones by test and analyze some specimens following the standards.